Influence of Customer Experience, Location, and Price On Loyalty Through Positive Word of Mouth on Customers of Kai Logistics Express DAOP IX - Diah Yulisetiarini; Olza Yahzunka Edcintha; Mochammad Farid Afandi (UNEJ e-Proceeding, 2021)
This study aims to determine the effect of customer experience, location, and price on customer loyalty through positive word of mouth on KAI Logistics Express DAOP IX service customers. The population of this study is KAI Logistics service customer Express DAOP IX . The sampling technique used is purposive sampling with a sample of 150 respondents. The analysis method used is path analysis. The results of this study showed that customer experience and location have no significant effect on the positive word of mouth in KAI Logistics DAOP IX service customers. Price has a significant effect on the positive word of mouth in KAI Logistics DAOP IX service customers. Customer experience has no significant effect on loyalty to KAI Logistics DAOP IX service customers. Location, price, and positive word of mouth affect loyalty to KAI Logistics DAOP IX service customers. Customer experience, location, and price through positive word of mouth have little indirect influence rather than direct influence. Keyword: Customer experience, location, loyalty, positive word of mouth, price.